Evaluasi User Experience SIPENA Menggunakan Metode User Experience Questionnaire - Budi Mas Aryawan, I Komang (Jurnal Ilmu Komputer; Vol 17 No 1 (2024): Jurnal Ilmu Komputer, 2024)
SIPENA is an employee attendance application regularly used by employees at the University of Udayana since the beginning of 2022. As a newly operational application, the quality of user experience becomes crucial in ensuring maximum adoption and acceptance from users. The use of the User Experience Questionnaire (UEQ) method is a relevant and effective approach, as UEQ can provide comprehensive measurement results of user experience with six scales, including: (1) attractiveness, (2) perspicuity, (3) efficiency, (4) dependability, (5) stimulation, and (6) novelty. Therefore, the research results can provide recommendations and guidance for the development and improvement of the application, which can offer greater added value for the institution in terms of efficiency and accuracy in attendance data management.